(untitled) (Vietnam Journal of Community Medicine, 2024)
Objective: To evaluate the effectiveness of nutritional Coloscare 24h 2+ product supplementation on nutritional status and health of kindergarten children. Subject and method: The intervention study with a control group. Sample size: 120 children aged 36-59 months for each groups. The intervention group supplementing Coloscare 24h 2+ twice a day for 2 months, and the control group with a regular diet. The study was completed in Ninh Binh in February 2024. Data collection and analyze were according to research indicators and by SPSS20.0 software. Results: The rate of respiratory infection was lower 31.7% (5.8% compared to 37.5) (p<0.05 ); the rate of diarrhea was lower 34.1% (4.2% vs. 38.3%) (p<0.05); the rate of constipation was lower 21.7% (0.8% vs 22.5%) (p<0.05); the rate of anorexia was lower 37.5% (4.2% vs. 41.7%) (p<0.05); the rate of difficulty sleeping was lower 11.6% (14.2% vs. 25.8%) (p<0.05). Weight was higher 0.49kg (0.75 ± 0.11kg vs. 0.26 ± 0.08kg) (p<0.05). Average of height was higher 0.52cm (1.57 ± 0.49cm vs. 1.05 ± 0.36cm) (p<0.05). The rate of malnutrition and risk of underweight malnutrition 14,2% (p<0,05); stunting 20,0% (p<0,05); child wasting 1,7% (p<0,05). The rate of underweight malnutrition 7,5% (p<0,05); stunting 6,7% (p<0,05) and wasting 1,7% (p<0,05). There was no overweight or obesity. The rate of drinking enough milk was 93.4% with 2 meals/day. Conclusion: Supplementing of Coloscare 24h 2+ product had nutritional positive effects on respiratory infection, improved digestion, anorexia, difficulty sleeping, weight, height and reduce the risk of malnutrition and malnutrition better than those of the control group and the rate of drinking enough milk were high.